PROSES ISLAMISASI DI NUSANTARA PADA ABAD KE-13 HINGGA KE-16: PERAN JALUR PERDAGANGAN, ULAMA, DAN INTERAKSI BUDAYA DALAM PENYEBARAN ISLAM - Agnes Secilia Simamora; Ellina Sianturi; Elman Wira Selamat Lafau; Imanuel Suranta Sembiring; Pristi Suhendro Lukitoyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The spread of Islam in the Indonesian archipelago was a gradual historical event influenced by numerous social, economic, and cultural factors. This study aims to examine the spread of Islam in the Indonesian archipelago from the 13th to the 16th century, focusing on trade routes, religious scholars, and cultural interactions in fostering the acceptance of Islamic teachings by the community. The method used in this research is a literature review, analyzing various historical sources, scientific journals, and writings relevant to this topic. The results indicate that international trade routes connecting the Indonesian archipelago with the Middle East, India, and China were one of the primary means by which Islam entered the archipelago, through Muslim traders. Furthermore, the role of religious scholars and religious figures in spreading the religion was crucial, introducing Islamic teachings through education, preaching, and the establishment of religious centers. Cultural interactions between local communities and Muslim immigrants also fostered acculturation, allowing Islamic teachings to be peacefully accepted by the Indonesian archipelago. Therefore, the spread of Islam in the Indonesian archipelago occurred not only through religious factors but was also influenced by the dynamics of trade, the preaching activities of religious scholars, and harmonious cultural interactions.